The Urgency of Positive Relationships in Fostering Learning Motivation - Apriliano, Moza; Shobahiya, Mahasri (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this research is to understand the importance of how positive relationships can foster student learning motivation and develop strategies that can improve positive relationships and learning motivation in the educational environment. This research was conducted at the KH Mas Mansur UMS Student Boarding School. This research uses a qualitative and field study approach, conducted directly in the field using objective data. Data collection techniques with observation are carried out in observation to be able to observe the object under study, interviews to collect some information and informants to obtain data, and documentation is used as supporting data to help obtain credible data. To test data credibility, researchers use triangulation, which can be interpreted as checking data from various sources in different ways and at various times, using triangulation of sources, techniques, and time. The results of this study explain the strategies for choosing positive relationships, the criteria for positive relationships referred to by students, and the importance of positive relationships in fostering learning motivation, there are five strategies, namely aligned goals and values, supportive friends, honesty and openness, commitment to education, avoidance of negative influences and indicators that can be classified that positive relationships are significant as evidenced in the discussion, namely cooperation, emotional support, healthy competition, role models, and exchange of ideas or inspiration.